2001
DOI: 10.1103/physrevc.64.044602
|View full text |Cite
|
Sign up to set email alerts
|

6Heinteraction with protons

Abstract: Experimental data for 6 Heϩ 1 H elastic scattering and the two-neutron transfer reaction, measured recently at the Joint Institute for Nuclear Research in Dubna, Russia, were analyzed by coupled channels calculations using a dineutron model of 6 He. The results of the analysis reveal that all the processes induced by 6 He on a hydrogen target are coupled. This analysis shows that the couplings to the 6 He→␣ϩ2n breakup channels can be included in a simple optical model calculation by means of a polarization pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 29 publications
(6 reference statements)
0
45
0
Order By: Relevance
“…These new data allow to better determine the nuclear interaction potential 6 He + p, which is an essential ingredient for the analysis of the transfer reaction, since it is necessary for the entrance channel in the DWBA calculation. Previous results obtained on 6 He + p elastic scattering in the same energy range have shown that the nucleon-nucleus optical models potentials used for stable nuclei have to be modified in the case of loosely bound nuclei such as 6 He [12,23]. Coupling to the continuum and to the resonant states are expected to play a significant role since the scattering states are much closer to the continuum states than in stable nuclei.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…These new data allow to better determine the nuclear interaction potential 6 He + p, which is an essential ingredient for the analysis of the transfer reaction, since it is necessary for the entrance channel in the DWBA calculation. Previous results obtained on 6 He + p elastic scattering in the same energy range have shown that the nucleon-nucleus optical models potentials used for stable nuclei have to be modified in the case of loosely bound nuclei such as 6 He [12,23]. Coupling to the continuum and to the resonant states are expected to play a significant role since the scattering states are much closer to the continuum states than in stable nuclei.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This approach previously used by Rusek et al [12,25] assumes a two body cluster model α+2n for the 6 He nucleus with the spin of the 2n cluster set to s=0. The wave functions Ψ 0 (r ) and Ψ 2 (r ) describing the relative motion of the two clusters in the 6 He ground state and the 6 He(2 + ) resonant state were calculated in potential wells whose depths were varied to reproduce respectively the binding energy of 0.975 MeV and the excitation energy of 1.8 MeV.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations